2013
DOI: 10.1007/s00245-013-9225-1
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion in Networks with Time-Dependent Transmission Conditions

Abstract: We study diffusion in a network which is governed by non-autonomous Kirchhoff conditions at the vertices of the graph. Also the diffusion coefficients may depend on time. We prove at first a result on existence and uniqueness using form methods. Our main results concern the long-term behavior of the solution. In the case when the conductivity and the diffusion coefficients match (so that mass is conserved) we show that the solution converges exponentially fast to an equilibrium. We also show convergence to a s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 9 publications
1
27
0
Order By: Relevance
“…The assertion about quasi‐contractivity is Laasri,, Prop. 2.1 whereas strong stability was proved by similar means in a special case in Arendt et al, Thm. 5.4…”
Section: Evolution Families: Notations and Preliminary Resultsmentioning
confidence: 99%
“…The assertion about quasi‐contractivity is Laasri,, Prop. 2.1 whereas strong stability was proved by similar means in a special case in Arendt et al, Thm. 5.4…”
Section: Evolution Families: Notations and Preliminary Resultsmentioning
confidence: 99%
“…Note that (A.6) with interface condition (2.10b) can be written as (A.9) with condition (A.11), and the differential operator A is self-adjoint and generates a compact, contractive and positive strongly continuous semigroup. Thus, by adjusting the scalar product to (A.12) and defining corresponding functions and operators based on the boundary conditions in (A.7), the analysis in [41] (see also [4,13]) can be borrowed to show that problem (A.6)-(A.7) with the initial data u 0 ∈ L p (G) has a unique classical solution for t > 0 that continuously depends on the initial data. The Schauder estimates in the assertion (ii) have been derived by [57].…”
Section: A2 Linear Parabolic Problemmentioning
confidence: 99%
“…Stability of steady states of parabolic equations were studied in [62,65]. More studies of diffusion equations in networks can be found in e.g., [4,30,31,63]. In these work, the model parameters are allowed to be time and/or space dependent; the so-called Kirchhoff laws or an excitatoric Kirchhoff condition (or dynamical node condition) are assumed at the interior connecting points.The goal of this paper is to establish a mathematically rigorous foundation of reaction-diffusionadvection equations defined on a metric tree network, which models population dynamics of a biological species on a river network.…”
mentioning
confidence: 99%
“…Sobolev spaces with values in a Banach space are quite natural objects and occur frequently while treating partial differential equations (see e.g. [Ama95], [Ama01], [DHP03], [CM09], [ADKF14]) and also in probability (see e.g. the upcoming monograph by Hytönen, van Neerven, Veraar and Weis [HvNVW16]).…”
Section: Introductionmentioning
confidence: 99%
“…Special attention is also given to the mapping F (x) = |x| where X is a Banach lattice, e.g. X = L r (Ω) or X = C(K) which occured in [ADKF14]. This mapping and more precisely differentiability properties of the projection onto a convex set in Hilbert space have also been studied by Haraux [Har77].…”
Section: Introductionmentioning
confidence: 99%